Position of Impacted Mandibular Third Molar in different Skeletal Facial Types - Sapkota, Manish Raj; Bhatta, Shishir; Shrestha, Sujita; Shrestha, Rabindra Man (Orthodontic Journal of Nepal, 2017)
Introduction: Variation in growth pattern in different facial forms affect the space available for tooth eruption, therefore the mandibular third molar impaction has correlation with different skeletal facial types. Objective: To determine the position of impacted mandibular third molar in different skeletal facial types in Nepalese samples. Materials & Method: This cross sectional study was carried out on pre-treatment lateral cephalogram and orthopantomogram records of 207 orthodontic patients visiting Kantipur Dental College and Hospital. Age range of the sample was 16-33 years. Various facial forms were determined with the help of mandibular plane angle (SN-GoGn); for which Nemoceph software was used. Beta angle was used to determine the angle of impaction of mandibular third molar. Impaction pattern was classified as per Pell & Gregory and Winter’s system. SPSS version 20 was used for statistical analysis. Result: Overall rate of mandibular third molar impaction was 63.77% (11.11% unilateral and 52.66% bilateral impaction). The most common type of impaction bilaterally was mesioangular based on Winter’s classification, Class II Position B based on Pell & Gregory’s classification. Higher rate of mandibular third molar impaction was found in dolichofacial type of face (49.2%). Conclusion: Decreased mandibular third molar impactions are seen in brachyfacial type compared to mesofacial and dolichofacial types